The Relationship between Evangelism and Discipleship According to Matthew 28:18-20 - Pardede, Lukman (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This research aims to determine the significant relationship between evangelism and discipleship of Christian religious education students at the Faculty of Teacher Training and Education, HKBP Nommensen University, Medan. This type of research is descriptive correlational. The population in this research is students of Christian Religious Education, Faculty of Teacher Training and Education, HKBP Nommensen University, Medan in 2022, totaling 39 people, while the sample in this research is 39 people with a collection technique using a total sample. The tool used in data collection was a questionnaire consisting of 28 items. For evangelism, 14 items were valid, while for discipleship, 14 items were valid, with 4 options before the questionnaire was used, its validity and reliability were tested. The research results state that student evangelism is moderate to 16 people (41%). Tendency to discipleship Students are categorized as moderate to 15 people (38.4%). According to Matthew 28:18-20 students, evangelism and discipleship have a significant relationship. This is obtained by tcount = 13.008 and ttable = 1.684, th>tt(13,008>1,684)where we get tcount>ttable. Thus, the relationship is significant and acceptable.